A Brazilian multicentre study on the clinical and epidemiological profiles of 1116 patients with amyotrophic lateral sclerosis and its phenotypic variants. Issue 5 (3rd July 2022) - Marques Couto, Christian; de Melo Queiroz, Elisa; Nogueira, Renata; Pires Duarte Küsel, Ana Paula; J. M. Nascimento, Osvaldo
Abstract: Objective: We conducted a multicentre, cross-sectional analysis of Brazilian patients with amyotrophic lateral sclerosis (ALS) and its phenotypic variants. We describe and compare their clinical and epidemiological data. Methods : We collected data from 1, 116 patients who visited seven rehabilitation hospitals in the SARAH network from 1 January 2009 to 20 March 2020. This representative sample of patients was from 308 cities in 25 states from the country's five regions. Results : The median age at onset was 55 years, and we found a significant linear correlation between the age at onset and the Municipal Human Development Index (MHDI) but not survival time. We found a four-year difference using a cutoff value of 0.750 ( p < 0.001). There was a male predominance, with a 1.2:1 sex ratio. The median time from onset to diagnosis was 17.6 months, and the most common phenotypic presentations were spinal-onset and bulbar-onset ALS (62.7% and 14.7%, respectively). In total, 12.9% of the patients had familial ALS, likely due to the overrepresentation of ALS type 8 patients in our population. Conclusions : In general, our numbers are consistent with most international series and with those of other Brazilian cohorts. When patients were analyzed according to their MHDI a considerable delay in symptom onset was found, suggesting the possibility of an environmental effect on these patients. Brazil has a longer diagnostic delay which is similar to other less-developed countries. This is a substantial concern and should be a priority for health authorities and neurology societies.